Database Systems for Advanced Applications 15th International Conference, DASFAA 2010, Tsukuba, Japan, April 1-4, 2010, Proceedings, Part I - Kitagawa, Hiroyuki; Ishikawa, Yoshiharu; Li, Qing.; Watanabe, Chiemi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This two volume set LNCS 5981 and LNCS 5982 constitutes the refereed proceedings of the 15th International Conference on Database Systems for Advanced Applications, DASFAA 2010, held in Tsukuba, Japan, in April 2010. The 39 revised full papers and 16 revised short papers presented together with 3 invited keynote papers, 22 demonstration papers, 6 industrial papers, and 2 keynote talks were carefully reviewed and selected from 285 submissions. The papers of the first volume are organized in topical sections on P2P-based technologies, data mining technologies, XML search and matching, graphs, spatialdatabases, XML technologies, time series and streams, advanced data mining, query processing, Web, sensor networks and communications, information management, as well as communities and Web graphs. The second volume contains contributions related to trajectories and moving objects, skyline queries, privacy and security, data streams, similarity search and event processing, storage and advanced topics, industrial, demo papers, and tutorials and panels.
Keynote Talks -- Knowledge on the Web: Robust and Scalable Harvesting of Entity-Relationship Facts -- Cloud Data Management @ Yahoo! -- P2P-Based Technologies -- Distributed Cache Indexing for Efficient Subspace Skyline Computation in P2P Networks -- iDISQUE: Tuning High-Dimensional Similarity Queries in DHT Networks -- Adaptive Ensemble Classification in P2P Networks -- Data Mining Technologies -- Mining Rare Association Rules in the Datasets with Widely Varying Items$1 (BFrequencies -- CAMLS: A Constraint-Based Apriori Algorithm for Mining Long Sequences -- PGP-mc: Towards a Multicore Parallel Approach for Mining Gradual Patterns -- Generalised Rule Mining -- XML Search and Matching -- An Effective Object-Level XML Keyword Search -- Effectively Inferring the Search-for Node Type in XML Keyword Search -- Matching Top-k Answers of Twig Patterns in Probabilistic XML -- Graphs -- NOVA: A Novel and Efficient Framework for Finding Subgraph Isomorphism Mappings in Large Graphs -- Efficiently Answering Probability Threshold-Based Shortest Path Queries over Uncertain Graphs -- Discovering Burst Areas in Fast Evolving Graphs -- Spatial Databases -- Answering Top-k Similar Region Queries -- Efficient Approximate Visibility Query in Large Dynamic Environments -- The Objects Interaction Matrix for Modeling Cardinal Directions in Spatial Databases -- Efficient Algorithms to Monitor Continuous Constrained k Nearest Neighbor Queries -- XML Technologies -- Chasing Tree Patterns under Recursive DTDs -- Efficient Label Encoding for Range-Based Dynamic XML Labeling Schemes -- An Efficient Parallel PathStack Algorithm for Processing XML Twig Queries on Multi-core Systems -- Keyword Search on Hybrid XML-Relational Databases Using XRjoin -- Efficient Database-Driven Evaluation of Security Clearance for Federated Access Control of Dynamic XML Documents -- Time Series and Streams -- Speeding Up Complex Video Copy Detection Queries -- Efficient Skyline Maintenance for Streaming Data with Partially-Ordered Domains -- A Simple, Yet Effective and Efficient, Sliding Window Sampling Algorithm -- Detecting Leaders from Correlated Time Series -- Advanced Data Mining -- Mining Outliers with Ensemble of Heterogeneous Detectors on Random Subspaces -- Mining Diversity on Networks -- Mining Regular Patterns in Data Streams -- Query Processing -- k-ARQ: k-Anonymous Ranking Queries -- QSQL: Incorporating Logic-Based Retrieval Conditions into SQL -- k-Selection Query over Uncertain Data -- Web -- Analysis of Implicit Relations on Wikipedia: Measuring Strength through Mining Elucidatory Objects -- Summarizing and Extracting Online Public Opinion from Blog Search Results -- Cloud as Virtual Databases: Bridging Private Databases and Web Services -- Temporal Top-k Search in Social Tagging Sites Using Multiple Social Networks -- Sensor Networks and Communications -- Air-Indexing on Error Prone Communication Channels -- Content-Based Multipath Routing for Sensor Networks -- Evaluating Continuous Probabilistic Queries Over Imprecise Sensor Data -- Information Management -- BPMN Process Views Construction -- Active Duplicate Detection -- FlexTable: Using a Dynamic Relation Model to Store RDF Data -- Communities and Web Graphs -- An MDL Approach to Efficiently Discover Communities in Bipartite Network -- Fires on the Web: Towards Efficient Exploring Historical Web Graphs -- Identifying Community Structures in Networks with Seed Expansion -- Dynamic Agglomerative-Divisive Clustering of Clickthrough Data for Collaborative Web Search.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Multimedia systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl.Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction